2014
DOI: 10.15252/embr.201439392
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 induces miR‐224/452 expression to drive EMT through TXNIP downregulation

Abstract: Malignant melanoma is highly lethal due to its aggressive invasive properties and metastatic dissemination. The transcription factor E2F1 is crucial for melanoma progression through poorly understood mechanisms. Here, we show that the miR-224/miR-452 cluster is significantly increased in advanced melanoma and invasive/ metastatic cell lines that express high levels of E2F1. miR-224/miR-452 expression is directly activated by E2F1 through transactivation of the GABRE gene. Ectopic expression of miR-224/miR-452 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 74 publications
5
66
0
Order By: Relevance
“…E2F1 may enhance metastatic behavior in melanomas by directly binding with VEGFC and the corresponding receptor VEGFR-3 for transactivation (37). The oncogenic properties of E2F1 have been associated with high EMT transition (38). However, the forces that drive E2F1 gene expression in ccRCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 may enhance metastatic behavior in melanomas by directly binding with VEGFC and the corresponding receptor VEGFR-3 for transactivation (37). The oncogenic properties of E2F1 have been associated with high EMT transition (38). However, the forces that drive E2F1 gene expression in ccRCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, we aim to explore patterns (mutual exclusivity or co-occurrence), focusing on components often altered in bladder cancer and involved in growth factor signaling, cell-cycle entry, and triggering of apoptosis in response to DNA damage with the focus on the E2F pathway. It has been shown recently that the E2F pathway is not only involved in the control of proliferation but also in invasion and metastasis (22)(23)(24), justifying the study of this pathway to explore invasiveness in bladder tumors.…”
Section: Assessing Phenotypesmentioning
confidence: 99%
“…As mentioned above, mutations of PIK3CA, but also deletions of CDKN1A (p21CIP) would drastically favour proliferation (Supplementary Tables S4 and S8). Recall that RB/E2F pathway is not only involved in proliferation but also in invasion and metastasis (22)(23)(24); thus, we anticipate that highly proliferative tumors are invasive ( Supplementary Fig. S2 shows that expression of gene targets of the E2F1-3 transcription factors is correlated to tumor stages).…”
Section: Data Interpretation Using the Modelmentioning
confidence: 99%
“…Previous studies have found that the oncogenic activity of miR-224 is exerted by targeting the 3′-UTR of TXNIP, which suppresses its expression [18]. Here, we discovered that both the mRNA and protein expression levels of TXNIP were significantly lower in all five PC cell lines tested than in normal pancreatic cells (Fig.…”
Section: Txnip Is a Direct Target Of Mir-224 In Pdac Cellsmentioning
confidence: 57%